For services rendered. The current status and future potential of markets for the ecosystem services provided by tropical forests / Scherr Sara,Andy White, Arvind Khare - Scherr, Sara (2004)
Reasons for interest in ecosystem service markets, lack of financial incentives to provide ecosystem services, the search for sustainable incomes in the tropical timber industry; status of min ecosystem services markets; benefits and risks to forest owners and producers, potential benefits; strategic issues for tropical countries, international competitiveness, legal and regulatory frameworks: key findings, current status of ecosystem service markets.